Agent-based simulation : canteen - Ang, Yew Kian (2012)
The aim of this project is to model an agent-based simulation which could accurately mimic the actual canteen environment of Nanyang Technology University, Food Connection. Modelling the simulated environment and agents depend strongly on what could be observed in the actual canteen.